Why do Europeans Migrate to Berlin? Social‐Structural Differences for Italian, British, French and Polish Nationals in the Period between 1980 and 2002*. (31st January 2011) - Verwiebe, Roland
Abstract: One of the main issues in migration research concerns the reasons migrants have for crossing borders. It is assumed in the research that migration is primarily economically driven. In recent studies, however, the importance of social and cultural reasons for migration has become apparent. In this context, the present contribution discusses the reasons for the migration of Europeans from Italy, France, the United Kingdom, and Poland who moved to Germany (Berlin) between 1980 and 2002. In this case, it can be shown empirically that purely economic reasons play a lesser role in migration than is generally assumed, whereas social and cultural motives actually have a much greater influence. Primary data gathered in Berlin early in 2002 form the empirical foundation of the study. Multinomial logistic regressions are used to discuss the function of social‐structural differences (e.g., nationality, age, gender, education, social origin) in the formation of individual reasons for migration.